Pengaruh Literasi Keuangan Dan Gaya Hidup Terhadap Perilaku Keuangan Mahasiswa STIE AMM Mataram - Janet Charina Kainde; I Nengah Arsana; I Gusti Gede Narung (Kredibel: Jurnal Ilmiah Manajemen, 2024)
This study aims to determine influence of financial literacy and lifestyle, both partially and simultaneously, on the financial behavior of STIE AMM Mataram students. The study employs a quantitative approach with an associative research design. The population includes all students of STIE AMM Mataram, totaling 1080 students from the 2021-2023 class. Sample of 92 students was selected using the accidental sampling technique. Data was collected through questionnaire utilizing a Likert scale ranging from 1 to 5. The data analysis was conducted using linear multiple regression analysis. Results of the study indicated that: (1) financial literacy and lifestyle partially has a significant effect on financial behavior, with t-stat (4.744) > t-table (1.987) and t-stat (4.210) > t-table (1.987) respectively; and (2) financial literacy and lifestyle simultaneously have a significant effect on financial behavior, with F-stat (45.861) > F-table (3.099).